2016
DOI: 10.1590/0037-8682-0070-2016
|View full text |Cite
|
Sign up to set email alerts
|

Performance of POC-CCA® in diagnosis of schistosomiasis mansoni in individuals with low parasite burden

Abstract: Introduction: Schistosomiasis, caused by Schistosoma mansoni, is a public health concern in Brazil. However, the most popular diagnostic method, the Kato-Katz technique, exhibits low sensitivity in low-endemicity areas. We aimed to compare the performance of an immunological assay, the point-of-care circulating cathodic antigen (POC-CCA®) test, with that of two parasitological techniques in a low-endemicity population. Methods: Our study included 141 individuals living in Estreito de Miralta, Minas Gerais, Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…In this case, undiagnosed individuals would not receive treatment, possibly develop serious disease, and contribute to maintenance of transmission. On the other hand, rMEA-IgG-ELISA showed 87.5% (56/64) of sensitivity in the group of ≤ 10 epg, which is indicative of the majority of cases of schistosome infection in Brazil [10-12, 20, 27, 28]. Additional studies utilizing other S.mansoni recombinant proteins also showed better results than K-K performed by 2 slides in low-endemic areas.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In this case, undiagnosed individuals would not receive treatment, possibly develop serious disease, and contribute to maintenance of transmission. On the other hand, rMEA-IgG-ELISA showed 87.5% (56/64) of sensitivity in the group of ≤ 10 epg, which is indicative of the majority of cases of schistosome infection in Brazil [10-12, 20, 27, 28]. Additional studies utilizing other S.mansoni recombinant proteins also showed better results than K-K performed by 2 slides in low-endemic areas.…”
Section: Discussionmentioning
confidence: 90%
“…In the majority of Brazilian endemic areas, transmission is maintained by individuals harboring low level infections that are undiagnosed by analysis of 2 slides of K-K in a single stool sample [6]. It has been suggested that a diagnostic test with high specificity and sensitivity will be needed for prevention, control and elimination of this disease [7, 12]. Some diagnostic methods have already shown their ability to detect positive individuals missed by parasitological techniques, due to low or absence of egg excretion [13, 14, 19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tests for the detection of circulating antigens have shown satisfactory results for the timely diagnosis, offering a promising complementary strategy to the traditional parasitological examination 42,43 . In this study, the positivity rate determined by the POC-CCA test was higher than that determined by the Kato-Katz technique, even with three slides.…”
Section: Discussionmentioning
confidence: 99%